Investigating the effect of the digital storytelling of peers’ childbirth experiences on the perception and mode of childbirth: a quasi-experimental study - Zahra Mahdavi; Leila Amiri-Farahani; Sally Pezaro; Hamid Salehiniya; Soghra Omrani Saravi (European Journal of Medical Research)
Abstract Background and aim Telling stories about giving birth vaginally can generate deeper understandings, potentially resulting in fewer requests to birth via cesarean section without medical reason. We aimed to determine the impact of the digital storytelling of peers’ childbirth experiences on the perception and mode of childbirth in those birthing for the first time. Methods This quasi-experimental study invited those pregnant and birthing for the first time from four comprehensive health centers to participate. Using a simple randomizing method, two centers were assigned to the control group and two centers were assigned to the intervention group. Convenience sampling was used to recruit 65 eligible participants from each center group. The six steps of the ASPIRE model were used to guide the development of the intervention. Five story-telling videos were sent weekly to participants in the intervention group to watch between the 32nd and 36th weeks of pregnancy. After giving birth, data were collected via telephone from those in both the control and intervention groups in relation to their mode of childbirth as a primary outcome. Furthermore, 7 to 21 days after giving birth, all participants completed the Childbirth Perception Scale as a primary outcome. Results Our subgroup analysis confirmed a statistically significant difference between both the intervention and control groups (P = 0.001), whereby those who gave birth vaginally in the intervention group indicated more positive perceptions of childbirth. Contrariwise, no significant difference was identified between the intervention and control groups in terms of perception of childbirth score in participants who gave birth via emergency cesarean section (P = 0.45). In all included participants, that is, those who experienced vaginal childbirth and those who experienced emergency cesarean section, there was no significant difference identified between the intervention and control groups in terms of perception of childbirth score (P = 0.088). Conclusion The digital storytelling of peers’ childbirth experiences is effective in cultivating more positive perceptions in relation to the experience of childbirth, specifically among those who experience childbirth vaginally. Considering the above, digital storytelling may be implemented as a useful tool in childbirth preparation, though the need for alternative interventions remains in pursuit of lowering the number of unnecessary births via cesarean section conducted overall.